Runtime verification : 6th International Conference, RV 2015 Vienna, Austria, September 22-25, 2015. Proceedings /: 6th International Conference, RV 2015 Vienna, Austria, September 22-25, 2015. Proceedings. (2015) - Unknown
No abstract available